Singular observation of a desirable change after bronchial artery embolization for hemoptysis in intracavitary aspergilloma - Prasad, B P K; Ray, Brijesh (Indian Journal of Radiology and Imaging, 2017)
Aspergillomas are fungal balls developing in pre-existing lung cavities, which are most commonly secondary to tuberculosis. Aspergillomas can cause hemoptysis due to erosion of the blood vessels in cavity walls, which can often be recurrent, massive, and life-threatening. Bronchial artery embolization is considered to be the treatment of choice for short-term control of hemoptysis, and lobectomy as the definitive treatment for aspergilloma. We present a unique observation in two cases of aspergilloma where the fungal balls disappeared radiologically after bronchial artery embolization performed for massive hemoptysis.
Keywords: Aspergilloma; bronchial artery embolization; hemoptysis